Spatial-behavioral types for concurrency and resource control in distributed systems - Caires, Luís (2019)
We would like to thank Luca Cardelli, Peter O’Hearn, Vasco Vasconcelos, Etienne Lozes and Gianluigi Ferrari for related discussions. We acknowledge CITI, Project POSC/55582/2004 SpaceTimeTypes, and IP Sensoria.